Investigation of the electroactive phase content and dielectric behaviour of mechanically stretched PVDF-GO and PVDF-rGO composites. (April 2020) - Mishra, Suvrajyoti; Sahoo, Rajesh; Unnikrishnan, Lakshmi; Ramadoss, Ananthakumar; Mohanty, Smita; Nayak, Sanjay Kumar
Graphical abstract: Highlights: PVDF-GO and PVDF-rGO composites were fabricated through solvent casting process followed by thermal compression and mechanical stretching. A maximum ß-phase content of 86% for PVDF-GO and 84% for PVDF-rGO was achieved for stretch ratio 2. PVDF/GO (ε = 28.5 and tanδ = 0.025) and PVDF/rGO (ε = 27.5 and tanδ = 0.015) composites exhibited excellent dielectric properties. Abstract: Piezoelectric and dielectric performance of polyvinylidenefluoride (PVDF) based composites are greatly influenced by the presence of electroactive polar ß-phase structure, which can be induced into PVDF matrix through mechanical stretching. Irrespective of numerous studies reported earlier, no literature has revealed the effect of mechanical stretching on the piezoelectric and dielectric behaviour of PVDF-Carbon-based fillers (Graphene Oxide-GO) and reduced Graphene Oxide-rGO)) reinforced composites. In this work, we have investigated the combined effect of chemical addition and mechanical deformation, on the improvement of electroactive ß-phase structure and dielectric behaviour of PVDF-GO/rGO composites. Maximum ß-phase content (86 % for PVDF-GO and 84 % for PVDF-rGO) with improved dielectric properties (Dielectric constant: 28.5 for PVDF-GO and 27.5 for PVDF-rGO, Dielectric loss: 0.025 for PVDF-GO and 0.015 for PVDF-rGO) have been achieved in such composites for stretch ratio 2. This behaviour is attributed to the strong interaction between PVDF and GO/rGO where maximum stress was distributed through uniform stretching force.